John Maynard Keynes - Davidson, Paul 1930- (Great thinkers in economics series, 2009)
This book looks at the life of Keynes leading up to the writing of his seminal General Theory , examines the General Theory in detail, and explores how it differs from classical theory. The impact of Keynes's work on the economy postwar and up to the present day is also assessed.